Improved PEM fuel cell performance with hydrophobic catalyst layers. (4th October 2018) - Avcioglu, Gokce S.; Ficicilar, Berker; Eroglu, Inci
Abstract: Flooding of catalyst layers is one of the major issues, which effects performance of low temperature proton exchange membrane fuel cells (PEMFC). Rendering catalyst layers hydrophobic one may improve the performance of PEMFC depending on Pt percentage in the catalyst and Polytetrafluoroethylene (PTFE) loading on the electrode. In this study, effect of hydrophobicity in catalyst layers on performance has been investigated by comparing performances of membrane electrode assemblies prepared with 48% Pt/C. Ultrasonic coating technique was used to manufacture highly efficient electrodes. Power density at 0.45 V increased by the addition of PTFE, from 0.95 to 1.01 W/cm 2 with H2 /O2 feed; while it slightly increased from 0.52 W/cm 2 to 0.53 W/cm 2 with H2 /Air feed. Addition of PTFE to catalyst layers while keeping Pt loading constant, enhanced performance providing improved water management. Kinetic activity increased by decreasing Nafion loading from 0.37 mg/cm 2 to 0.25 mg/cm 2 while introducing PTFE (0.12 mg/cm 2 ) to the electrode. Electrochemical impedance spectroscopy (EIS) results proved that charge transfer resistance decreased with hydrophobic catalyst layers for H2 /O2 feed. This is attributed to enhanced water management due to PTFE presence. Highlights: 48 wt % Pt/C is a promising catalyst for hydrophobic catalyst layers. Optimum PTFE loading for hydrophobic catalyst layer is 0.12 mg/cm 2 . Inclusion of PTFE on both catalyst layers is preferable for improved performances.